Tetraphenyl ornamented carbazolyl disubstituted diphenyl sulfone as bipolar TADF host for highly efficient OLEDs with low efficiency roll-offs. (October 2021) - Gudeika, Dalius; Bezvikonnyi, Oleksandr; Masimukku, Naveen; Volyniuk, Dmytro; Chen, Chia-Hsun; Ding, Wen-Cheng; Lee, Jiun-Haw; Chiu, Tien-Lung; Grazulevicius, Juozas V.
Abstract: Highly efficient organic light emitting diodes based on thermally activated delayed fluorescence were fabricated using 9, 9'-(sulfonylbis([ 1, 1':3′, 1″-terphenyl ]-5′, 2′-diyl))bis(9 H -carbazole) as a host. The best device demonstrated high maximum external quantum efficiency of 23.3%, maximum current efficiency of 67.7 cd/A, maximum power efficiency of 60.9 lm/W with low efficiency roll-off. These characteristics were achieved due to the utilization of bipolar TADF host with tetraphenyl ornamenting. The molecular design strategy used allowed to obtain OLED host with the required combination of properties, i.e. triplet harvesting ability, perfect host→guest energy transfer, emission not affected by intermolecular interaction (no excimer/exciplex formation), high triplet level (2.98 eV), bipolar charge transporting properties, thermal stability up to sublimation temperature of 467 °C, amorphous forming properties with high glass transition temperature of 153 °C, good charge injecting properties (ionization potential of 5.9 eV and electron affinity of 2.8 eV). When the compound was used as TADF emitter, practically the same electroluminescent spectra peaked at 430 nm were obtained for deep-blue OLEDs with both non-doped and doped emitting layers. Such untypical electroluminescent behaviour of TADF OLEDs is attributed to the restricted by phenyl substituents changes of dihedral angels between donor and acceptor moieties and to reduced posibilities of the formation of the different conformers and aggregates in solid state. Graphical abstract: Image 1 Highlights: Design strategy of compounds with "frozen" TADF properties. Doped and non-doped OLEDs with similar colors of their electroluminescence. Derivative of tetraphenyl ornamented diphenyl sulfone and carbazole as OLED host. TADF devices with high maximum external quantum efficiency of 23.3%. Low roll-off efficiency resulting in EQE of 22.3% at 1000 cd/m 2 .